High-wear-resistance waste tire rubber powder-based friction layer, preparation method thereof and application of friction layer in friction nano generator
By using the high wear-resistant friction layer prepared by using waste tire rubber powder, wood fiber and basalt fiber, the problem of insufficient wear resistance of the existing friction layer is solved, the power generation effect of friction nanogenerators is improved, and the waste tire rubber powder is promoted. Comprehensive use of.
Patent Information
- Application Number
- CN202411744856.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The wear resistance of existing polymer material-based friction layers is insufficient, which limits the application potential of friction nanogenerators in long-term energy collection and monitoring, and the comprehensive utilization rate of used tire rubber is low.
Use waste tire powder, wood fiber and basalt fiber as raw materials to prepare a high wear-resistant waste tire powder-based friction layer through grafting reaction, fluorination treatment and composite solution curing, and is used in friction nanogenerators.
It significantly improves the wear resistance and mechanical properties of the friction layer, improves the power generation effect of friction nanogenerators, and provides theoretical support for the application of waste tire rubber powder in micro-nano energy in road traffic infrastructure.
Smart Images

Figure CN119410001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of friction nanogenerator power generation, and specifically relates to a highly wear-resistant waste tire rubber powder-based friction layer, a preparation method thereof, and an application in a friction nanogenerator. Background Art
[0002] With the continuous development of intelligent transportation systems, people's demand for safety and convenience is increasing, which has significantly increased the requirements for sensor accuracy. At the same time, the number of sensor nodes required by the system has also increased sharply. Although wireless transmission technology has effectively reduced the complexity of wiring and enabled sensor signals to be smoothly delivered to the terminal, the power supply of sensor nodes still relies on traditional power supplies, which have limited service life and are difficult to replace and maintain batteries. In recent years, friction nanogenerators (TENGs) based on the principles of friction charging and electrostatic induction have emerged as a smarter and more environmentally friendly solution that can convert mechanical energy into electrical energy for long-term monitoring of transportation infrastructure such as asphalt pavement.
[0003] At present, polymer materials, such as polytetrafluoroethylene, polyvinylidene fluoride, polydimethylsiloxane and polyethylene terephthalate, dominate the friction layer materials of TENG due to their unique functional groups and physical and chemical properties. However, the insufficient wear resistance of these polymers limits the application potential of TENG in long-term energy collection and monitoring. Therefore, the research and development of friction layer materials with high wear resistance has become a core challenge in promoting the high-quality development of triboelectric power generation technology. On the other hand, the issue of waste tire rubber has become a focus of global attention, and how to solve the problem of waste tire rubber treatment and realize its comprehensive utilization is also a challenge. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problems of low comprehensive utilization rate of existing waste tire rubber and low power generation performance of high molecular polymer-based friction layer, and to provide a highly wear-resistant waste tire rubber powder-based friction layer and its preparation method and application in friction nanogenerator.
[0005] One of the purposes of the present invention is to provide a method for preparing a highly wear-resistant waste tire rubber powder-based friction layer, the method being carried out according to the following steps:
[0006] Step 1: adding waste tire rubber powder and initiator into deionized water, heating to a certain temperature under stirring, then dropping an aqueous solution of hydroxylated monomer to carry out grafting reaction, filtering and vacuum drying after the reaction, extracting with acetone as an extractant, filtering and vacuum drying again after extraction to obtain hydroxylated grafted waste tire rubber powder;
[0007] Step 2: dissolving the hydroxylated grafted waste tire rubber powder in N,N-dimethylformamide (DMF), then adding wood fiber, stirring magnetically at a certain temperature for a certain time, filtering and vacuum drying the solid product to obtain hydroxylated rubber powder / wood fiber, then dripping a fluorination agent, heating in a vacuum drying oven for fluorination, and obtaining fluorinated rubber powder;
[0008] Step 3: Dissolve the fluorinated rubber powder in DMF, then add silane coupling agent, titanium dioxide (TiO2) and basalt fiber powder, and stir magnetically at a certain temperature for a certain period of time to obtain a uniform rubber powder-basalt fiber composite solution, which is then placed in a mold to remove bubbles and solidify into a film under vacuum conditions to obtain a highly wear-resistant waste tire rubber powder-based friction layer.
[0009] It is further defined that the initiator in step 1 is potassium persulfate, ammonium persulfate or benzoyl peroxide.
[0010] It is further defined that the hydroxylated monomer in step 1 is hydroxyethyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.
[0011] It is further defined that in step 1, the mass ratio of the initiator, the hydroxylated monomer and the waste tire rubber powder is (10-20): (10-20):100.
[0012] It is further defined that the grafting reaction temperature in step 1 is 80-100° C. and the time is 1-4 hours.
[0013] It is further defined that in step 2, the wood fiber is 20-40wt% of the hydroxylated grafted waste tire rubber powder.
[0014] It is further defined that in step 2, magnetic stirring is performed at 400-600 rpm and 50-70° C. for 2-4 hours.
[0015] It is further defined that the fluorination agent in step 2 comprises perfluorooctylethyltriethoxysilane (PFOTES).
[0016] It is further defined that the fluorination temperature in step 2 is 90-110° C. and the time is 2-4 hours.
[0017] It is further defined that the contents of fluorinated rubber powder, silane coupling agent, titanium dioxide (TiO2) and basalt fiber powder in the rubber powder-basalt fiber composite solution in step 3 are 10-20wt%, 1-2wt%, 1-2wt% and 1-2wt%, respectively.
[0018] It is further defined that in step 3, the silane coupling agent comprises 3-thiopropylmethoxysilane.
[0019] It is further defined that in step 3, magnetic stirring is performed at 400-600 rpm and 50-70° C. for 2-4 hours.
[0020] It is further defined that in step 3, the curing temperature is 60-80°C and the curing time is 12-24 hours.
[0021] A second object of the present invention is to provide a highly wear-resistant scrap tire rubber powder-based friction layer obtained by the above method.
[0022] The third object of the present invention is to provide a use of a highly wear-resistant waste tire rubber powder-based friction layer obtained by the above method in a friction nanogenerator.
[0023] A fourth object of the present invention is to provide a friction nanogenerator, wherein the negative electrode of the friction nanogenerator comprises the above-mentioned highly wear-resistant waste tire rubber powder-based friction layer, and the positive electrode comprises a PA film.
[0024] A fifth object of the present invention is to provide a method for preparing a triboelectric nanogenerator, the method comprising the following steps:
[0025] S1: Paste the above-mentioned high wear-resistant waste tire rubber powder-based friction layer film onto a copper electrode, and then paste the other side of the copper electrode onto an acrylic plate to prepare a negative electrode;
[0026] S2: Paste the PA film onto the copper electrode, and then paste the other side of the copper electrode onto the acrylic plate to prepare a positive electrode;
[0027] S3: Connect the four corners of the two acrylic plates with springs to obtain a rubber powder / PA friction nanogenerator.
[0028] Compared with the prior art, the present invention has the following significant effects:
[0029] The present invention uses waste tire rubber powder, wood fiber, and basalt fiber as raw materials to prepare a highly wear-resistant waste tire rubber powder-based friction layer for use in a friction nanogenerator, which not only greatly improves the power generation effect, but also significantly improves the wear resistance and mechanical properties of the friction layer, and also provides theoretical support for the application of waste tire rubber powder in micro-nano energy for road traffic infrastructure. By introducing wood fiber, the lignin in the wood fiber is used to increase the degree of fluorination of the rubber powder, further improving the power generation performance. In addition, the cellulose of the wood fiber plays a major supporting role as a mesh skeleton that constitutes the microfibers as the fiber cell wall, is insoluble in DMF solution, and works together with the basalt fiber to play a role in reinforcement and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the configuration of the friction nanogenerator;
[0031] Figure 2 for Figure 1 Schematic diagram of the structure of the positive friction layer and the negative friction layer;
[0032] Figure 3This is a connection diagram of the friction nanogenerator test system;
[0033] Figure 4 for Figure 3 Schematic diagram of the structure of the middle movement module;
[0034] In the accompanying drawings, the components represented by the reference numerals are as follows:
[0035] 1-Acrylic plate A, 2-Conductive copper electrode A, 3-Negative friction layer, 4-Acrylic plate B, 5-Conductive copper electrode B, 6-Positive friction layer, 7-Support spring, 8-Bottom plate, 9-Integrated drive-controlled stepper motor, 10-Motion module, 11-Movers, 12-Stators, 13-Power supply, 14-Computer, 15-Acquisition module, 16-Electrometer, 17-Motion module. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0038] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0039] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0041] Embodiment 1: The preparation method of the highly wear-resistant waste tire rubber powder-based friction layer of this embodiment is carried out according to the following steps:
[0042] Step 1: Wash and dry the waste tire rubber powder (Shijiazhuang Jinli Mining Co., Ltd.) with deionized water and acetone respectively, and repeat the washing and drying operation 3 times to remove oil, dust and old adhesive residues in the waste tire rubber powder; sieve the washed waste tire rubber powder to ensure that the mesh number of the waste tire rubber powder is 200 mesh.
[0043] In a three-necked flask equipped with a condenser, mechanical stirring and thermometer, add 25g of waste tire rubber powder and 100g of deionized water, add 5g of potassium persulfate, mix well, stir, and heat to 80°C; dissolve 5g of hydroxyethyl acrylate in 50mL of deionized water and add dropwise to the three-necked flask within 1h for reaction, the reaction time is 4h, filter after the reaction, dry under vacuum conditions of 0.1MPa and 40°C to obtain a crude grafted product; extract the crude grafted product with acetone as the extractant for 24h, then filter, and dry the filtrate to constant weight under vacuum conditions of 0.1MPa and 40°C to obtain hydroxylated grafted waste tire rubber powder.
[0044] Step 2: Weigh 25g of hydroxylated grafted waste tire rubber powder and 10g of wood fiber (Wenan Xinbao Cellulose Co., Ltd.) and dissolve them in 65g of DMF solution. After mixing, place them in a magnetic stirrer and stir them at 500rpm at 60℃ for 3h to obtain rubber powder / wood fiber solution. Dry them to constant weight under vacuum at 0.1MPa and 40℃ to obtain hydroxylated rubber powder / wood fiber.
[0045] 10 g of PFOTES reagent was dropped into the hydroxylated rubber powder / wood fiber, and heated for 3 h under vacuum conditions of 0.1 MPa and 100°C to obtain fluorinated rubber powder.
[0046] Step 3: Dissolve 20g of fluorinated rubber powder in 74g of DMF solution, mix and place in a magnetic stirrer at 60°C and 500rpm for 6h to obtain a rubber powder / DMF solution. Add 2g of 3-thiopropylmethoxysilane, 2g of TiO2 powder and 2g of 500-mesh basalt fiber powder (Taian Haoda New Materials Co., Ltd.) to the rubber powder / DMF solution, continue to place in a magnetic stirrer at 60°C and 500rpm for 5h to obtain a uniform rubber powder-basalt fiber composite solution. Finally, place the rubber powder-basalt fiber composite solution in a 3D printed mold, place it in a vacuum oven to remove bubbles, the vacuum degree is 0.1MPa, and cure at 70°C for 24h to obtain a 100μm thick high wear-resistant waste tire rubber powder-based film (such as Figure 2 shown).
[0047] Application example 1: Combination Figure 1The preparation method of the friction nanogenerator comprises the following steps:
[0048] First, the high wear-resistant waste tire rubber powder-based film and PA film of Example 1 were cut into 2cm*2cm pieces;
[0049] Secondly, a highly wear-resistant waste tire rubber powder-based film is pasted onto a conductive copper electrode, and then the other side of the copper electrode is pasted onto an acrylic plate to prepare a negative electrode;
[0050] Then, the PA film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a positive electrode.
[0051] Finally, the two acrylic plates were connected at the four corners with springs to obtain the rubber powder / PA friction nanogenerator.
[0052] Combination Figure 3-4 , a friction nanogenerator test system was built by ourselves to test the friction nanogenerator. During the test, the positive electrode was pasted on the vertical plate of the stator 12 in the motion module 17, and the negative electrode was pasted on the vertical plate of the mover 11 in the motion module 17. The Keithley6517B electrometer 16, motion module 17, and acquisition module 15 were controlled, and the current and voltage signals obtained in the test were sampled at a high frequency using a high-speed signal acquisition card.
[0053] The friction nanogenerator of Application Example 1 still maintains stable output characteristics after being excited 20,000 times at 10 Hz, and its output voltage peak is 280V.
[0054] Embodiment 2: The preparation method of the highly wear-resistant scrap tire rubber powder-based friction layer of this embodiment is carried out according to the following steps:
[0055] Step 1: Wash and dry the waste tire rubber powder (Shijiazhuang Jinli Mining Co., Ltd.) with deionized water and acetone respectively, and repeat the washing and drying operation 3 times to remove oil, dust and old adhesive residues in the waste tire rubber powder; sieve the washed waste tire rubber powder to ensure that the mesh number of the waste tire rubber powder is 200 mesh.
[0056] In a three-necked flask equipped with a condenser, mechanical stirring and thermometer, add 25g of waste tire rubber powder and 100g of deionized water, add 5g of potassium persulfate, mix well, stir, and heat to 80°C; dissolve 5g of hydroxyethyl acrylate in 50mL of deionized water and add dropwise to the three-necked flask within 1h for reaction, the reaction time is 4h, filter after the reaction, dry under vacuum conditions of 0.1MPa and 40°C to obtain a crude grafted product; extract the crude grafted product with acetone as the extractant for 24h, then filter, and dry the filtrate to constant weight under vacuum conditions of 0.1MPa and 40°C to obtain hydroxylated grafted waste tire rubber powder.
[0057] Step 2: Weigh 25g of hydroxylated grafted waste tire rubber powder and 10g of wood fiber (Wenan Xinbao Cellulose Co., Ltd.) and dissolve them in 65g of DMF solution. After mixing, place them in a magnetic stirrer and stir them at 500rpm at 60℃ for 3h to obtain rubber powder / wood fiber solution. Dry them to constant weight under vacuum at 0.1MPa and 40℃ to obtain hydroxylated rubber powder / wood fiber.
[0058] 10 g of PFOTES reagent was dropped into the hydroxylated rubber powder / wood fiber, and heated for 3 h under vacuum conditions of 0.1 MPa and 100°C to obtain fluorinated rubber powder.
[0059] Step 3: Dissolve 10g of fluorinated rubber powder in 87g of DMF solution, mix and place in a magnetic stirrer at 60°C and 500rpm for 6h to obtain a rubber powder / DMF solution. Add 1g of 3-thiopropylmethoxysilane, 1g of TiO2 powder and 1g of 500-mesh basalt fiber powder (Taian Haoda New Materials Co., Ltd.) to the rubber powder / DMF solution, and continue to place in a magnetic stirrer at 60°C and 500rpm for 5h to obtain a uniform rubber powder-basalt fiber composite solution. Finally, the rubber powder-basalt fiber composite solution is placed in a 3D printed mold, placed in a vacuum oven to remove bubbles, the vacuum degree is 0.1MPa, and cured at 70°C for 24h to obtain a 100μm thick high wear-resistant waste tire rubber powder-based film (such as Figure 2 shown).
[0060] Application Example 2: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:
[0061] First, the high wear-resistant waste tire rubber powder-based film and PA film of Example 2 were cut into 2cm*2cm pieces;
[0062] Secondly, a highly wear-resistant waste tire rubber powder-based film is pasted onto a conductive copper electrode, and then the other side of the copper electrode is pasted onto an acrylic plate to prepare a negative electrode;
[0063] Then, the PA film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a positive electrode.
[0064] Finally, the two acrylic plates were connected at the four corners with springs to obtain the rubber powder / PA friction nanogenerator.
[0065] The electrical output performance test method is the same as that in Application Example 1. The triboelectric nanogenerator of Application Example 2 still maintains stable output characteristics after 10 Hz and 18,000 excitations, and its output voltage peak value is 220V.
[0066] Comparative Example 1: The preparation method of the pure PTFE film of this embodiment is carried out according to the following steps:
[0067] Weigh 20g of PTFE powder and dissolve it in 80g of THF solution. After mixing well, place the solution in a magnetic stirrer at 60°C and 500rpm for 3h to obtain a PTFE-THF solution. Place the PTFE-THF solution in a 3D printed mold, put it in a vacuum oven to remove bubbles, and cure it at 70°C for 24h to obtain a 100μm thick pure PTFE film (such as Figure 2 shown).
[0068] Comparative application example 1: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:
[0069] First, the pure PTFE film and PA film of Comparative Example 1 were cut into 2 cm*2 cm pieces;
[0070] Secondly, the pure PTFE film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a negative electrode.
[0071] Then, the PA film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a positive electrode.
[0072] Finally, the two acrylic plates were connected at the four corners with springs to obtain the PTFE / PA friction nanogenerator.
[0073] The electrical output performance test method is the same as that in Application Example 1. The maximum open circuit voltage and mechanical properties of Example 1 and Comparative Example 1 were tested. Compared with Application Example 1, the output characteristics of the friction nanogenerator decreased after 10 Hz and 15,000 excitations, and its output voltage peak was 195V.
[0074] Comparative Example 2: The preparation method of the waste tire rubber powder-based film of this embodiment is carried out according to the following steps:
[0075] Step 1: Wash and dry the waste tire rubber powder (Shijiazhuang Jinli Mining Co., Ltd.) with deionized water and acetone respectively, and repeat the washing and drying operation 3 times to remove oil, dust and old adhesive residues in the waste tire rubber powder; sieve the washed waste tire rubber powder to ensure that the mesh number of the waste tire rubber powder is 200 mesh.
[0076] In a three-necked flask equipped with a condenser, mechanical stirring and thermometer, add 25g of waste tire rubber powder and 100g of deionized water, add 5g of potassium persulfate, mix well, stir, and heat to 80°C; dissolve 5g of hydroxyethyl acrylate in 50mL of deionized water and add dropwise to the three-necked flask within 1h for reaction, the reaction time is 4h, filter after the reaction, dry under vacuum conditions of 0.1MPa and 40°C to obtain a crude grafted product; extract the crude grafted product with acetone as the extractant for 24h, then filter, and dry the filtrate to constant weight under vacuum conditions of 0.1MPa and 40°C to obtain hydroxylated grafted waste tire rubber powder.
[0077] Step 2: Add 10 g of PFOTES reagent to the hydroxylated rubber powder / wood fiber, and heat for 3 h at 100° C. under vacuum conditions of 0.1 MPa to obtain fluorinated rubber powder.
[0078] Step 3: Dissolve 20g of fluorinated rubber powder in 74g of DMF solution, mix and place in a magnetic stirrer at 60°C and 500rpm for 6h to obtain a rubber powder / DMF solution. Add 2g of 3-thiopropylmethoxysilane, 2g of TiO2 powder and 2g of 500-mesh basalt fiber powder (Taian Haoda New Materials Co., Ltd.) to the rubber powder / DMF solution, continue to place in a magnetic stirrer at 60°C and 500rpm for 5h to obtain a uniform rubber powder-basalt fiber composite solution. Finally, place the rubber powder-basalt fiber composite solution in a 3D printed mold, place it in a vacuum oven to remove bubbles, the vacuum degree is 0.1MPa, and cure at 70°C for 24h to obtain a 100μm thick waste tire rubber powder-based film (such as Figure 2 shown).
[0079] Comparative application example 2: Combination Figure 1 The preparation method of the friction nanogenerator comprises the following steps:
[0080] First, the waste tire rubber powder-based film and PA film of Comparative Example 2 were cut into 2cm*2cm pieces;
[0081] Secondly, the waste tire rubber powder-based film is pasted on the conductive copper electrode, and then the other side of the copper electrode is pasted on the acrylic plate to prepare a negative electrode;
[0082] Then, the PA film was pasted onto the conductive copper electrode, and the other side of the copper electrode was pasted onto an acrylic plate to prepare a positive electrode.
[0083] Finally, the two acrylic plates were connected at the four corners with springs to obtain the rubber powder / PA friction nanogenerator.
[0084] The electrical output performance test method is the same as that in Application Example 1. The maximum open circuit voltage and mechanical properties of Example 1 and Comparative Example 2 were tested. Compared with Application Example 2, the output characteristics of the friction nanogenerator decreased after 10 Hz and 18,000 excitations, and its output voltage peak was 226V.
[0085] The reason for the above phenomenon is that no wood fiber is added in Comparative Example 2, while in Example 1, wood fiber is added in step 2. The lignin in the wood fiber is dissolved in the DMF solution. In addition to hydroxylating the hydroxyl groups of the waste tire rubber powder, the lignin makes the rubber powder more fluorinated. Therefore, the power generation performance of Example 1 is better than that of Comparative Example 2. In addition, the cellulose of the wood fiber plays a major supporting role as a mesh skeleton of the fiber cell wall, which is insoluble in the DMF solution and works together with the basalt fiber to play a role in reinforcement and wear resistance. Therefore, after 18,000 excitations, the output characteristics of the friction nanogenerator of Comparative Example 2 began to decay, and the mechanical properties were lower than those of Example 1.
[0086] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a highly wear-resistant waste tire rubber powder-based friction layer, characterized in that: The method: Step 1: adding waste tire rubber powder and initiator into deionized water, heating to a certain temperature under stirring, then dropping an aqueous solution of hydroxylated monomer to carry out grafting reaction, filtering and vacuum drying after the reaction, extracting with acetone as an extractant, filtering and vacuum drying again after extraction to obtain hydroxylated grafted waste tire rubber powder; Step 2: dissolving the hydroxylated grafted waste tire rubber powder in DMF, then adding wood fiber, stirring magnetically at a certain temperature for a certain time, filtering and vacuum drying the solid product to obtain hydroxylated rubber powder / wood fiber, then dripping a fluorination agent, heating in a vacuum drying oven for fluorination, and obtaining fluorinated rubber powder; Step 3: Dissolve the fluorinated rubber powder in DMF, then add silane coupling agent, TiO2 and basalt fiber powder, and stir magnetically at a certain temperature for a certain period of time to obtain a uniform rubber powder-basalt fiber composite solution, which is then placed in a mold to remove bubbles and solidify into a film under vacuum conditions to obtain a highly wear-resistant waste tire rubber powder-based friction layer.
2. The method according to claim 1, characterized in that In step 1, the initiator is potassium persulfate, ammonium persulfate or benzoyl peroxide, the hydroxylated monomer is hydroxyethyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate, and the mass ratio of the initiator, the hydroxylated monomer and the waste tire rubber powder is (10-20): (10-20):
100.
3. The method according to claim 1, characterized in that: In step 1, the grafting reaction temperature is 80-100° C. and the time is 1-4 hours.
4. The method according to claim 1, characterized in that: In step 2, the wood fiber is 20-40wt% of the hydroxylated grafted waste tire rubber powder, and is magnetically stirred at 400-600rpm at 50-70°C for 2-4h. The fluorination agent includes PFOTES, the fluorination temperature is 90-110°C, and the time is 2-4h.
5. The method according to claim 1, characterized in that In step 3, the contents of fluorinated rubber powder, silane coupling agent, TiO2 and basalt fiber powder in the rubber powder-basalt fiber composite solution are 10-20wt%, 1-2wt%, 1-2wt% and 1-2wt%, respectively, and the silane coupling agent includes 3-thiopropylmethoxysilane.
6. The method according to claim 1, characterized in that In step 3, magnetic stirring is performed at 50-70° C. at a speed of 400-600 rpm for 2-4 hours, the curing temperature is 60-80° C., and the curing time is 12-24 hours.
7. A highly wear-resistant scrap tire rubber powder-based friction layer obtained by the method according to any one of claims 1 to 6.
8. Use of the highly wear-resistant scrap tire rubber powder-based friction layer according to claim 7 in a friction nanogenerator.
9. A friction nanogenerator, characterized in that: The negative electrode of the friction nanogenerator comprises the highly wear-resistant waste tire rubber powder-based friction layer as described in claim 7, and the positive electrode comprises a PA film.
10. The method for preparing the triboelectric nanogenerator according to claim 9, characterized in that: The method steps are as follows: S1 pastes a highly wear-resistant scrap tire rubber powder-based friction layer film onto a copper electrode, and then pastes the other side of the copper electrode onto an acrylic plate to prepare a negative electrode; S2: Paste the PA film onto the copper electrode, and then paste the other side of the copper electrode onto the acrylic plate to prepare a positive electrode; S3: Connect the four corners of the two acrylic plates with springs to obtain a rubber powder / PA friction nanogenerator.
Citation Information
Patent Citations
PVDF@KUAST-8 nanofiber composite film for friction nanogenerator and preparation method of film
CN111118619A
Modified triboelectrification material for triboelectric nano-generator, preparation method of modified triboelectrification material and triboelectric nano-generator
CN116239812A
Basalt-fluoroplastic composite material for tribotechnical purposes
RU2013118286A
Flexible hybrid generator, preparation method therefor and use thereof, and flexible self-charging device
WO2021237908A1